Artefact: An R implementation of the autospearman function - JIARPAKDEE, Jirayus (Institutional Knowledge at Singapore Management University, 2018)
This artefact is the implementation of AutoSpearman, an automated metric selection approach based on correlation analyses. The goal of AutoSpearman is to automatically mitigate correlated metrics prior to constructing analytical models. This artefact is implemented as an R package and is available in the GitHub repository. We provide descriptions and R code snippets for the installation of AutoSpearman and usage examples.